Dynamics of a fixed bed adsorption column in the kinetic separation of hexane isomers in MOF ZIF-8 - Mendes, Patrícia A.P. (2018)
A fixed bed adsorption mathematical model has been developed to de- scribe the kinetic separation of hexane isomers when they flow through a packed bed containing the microporousMetal-Organic Framework (MOF) ZIF-8 adsorbent. The flow of inert and adsorbable species through the fixed bed is modeled with fun- damental differential equations according to the mass and heat conservation laws, a general isotherm to describe adsorption equilibrium and a lumped kinetic mass transfer mechanism between bulk gas phase and the porous solid. It is shown that a proper combination of two characteristic times (the residence time of the gas in the fixed bed, fb and the characteristic time of diffusion of solutes into the pores dif ) can lead to very different dynamics of fixed bed adsorbers where in a limiting case can gives rise to a spontaneous breakthrough curves of solutes. The numerical simulations of an experimental breakthrough curve with the developed mathemati- cal model clearly explain the complete separation between linear n-Hexane (nHEX) and the respective branched isomers: 3-Methyl-Pentane (3MP) and 2, 2-Dimethyl- Butane (22DMB). The separation is due to significant differences in the diffusivity parameters dif between 3MP and 22DMB and the residence time of the gas mixture fb within the fixed bed. This work shows the importance of mathematical modelling for the comprehension and design of adsorption separation processes.